Paracetamol/Acetaminophen (Single Administration) for Perineal Pain in the Early Postpartum Period - Chou, D.; Abalos, E.; Gyte, G. M.; Gulmezoglu, A. M. (2012)
BACKGROUND: Perineal pain is a common but poorly studied adverse outcome following childbirth. Pain may result from perineal trauma due to bruising, spontaneous tears, surgical incisions (episiotomies), or in association with operative births (ventouse or forceps assisted births). OBJECTIVES: To determine the efficacy of a single administration of paracetamol (acetaminophen) systemic drugs used in the relief of acute postpartum perineal pain SEARCH STRATEGY: We searched the Cochrane Pregnancy and Childbirth Group's Trials Register (December 2009). SELECTION CRITERIA: Randomised controlled trials (RCTs) assessing paracetamol (acetaminophen) in a single dose compared with placebo for women with early postpartum perineal pain. We excluded quasi-RCTs and cross-over studies. DATA COLLECTION AND ANALYSIS: Two review authors assessed each paper for inclusion and extracted data. One review author reviewed the decisions and confirmed calculations for pain relief scores. MAIN RESULTS: We have included 10 studies describing two dosages of paracetamol. Of these, five studies (526 women) assessed 500 mg to 650 mg and six studies (841 women) assessed 1000 mg of paracetamol. We chose to use random-effects meta-analyses because of the heterogeneity in dosage used. Studies were from the 1970s to the early 1990s, and there was insufficient information to assess the risk of bias adequately, hence the findings need to be interpreted within this context.More women experienced pain relief with paracetamol compared with placebo (average risk ratio (RR) 2.14, 95% confidence interval (CI) 1.59 to 2.89, 10 studies, 1279 women). In addition, there were significantly fewer women having additional pain relief with paracetamol compared with placebo (RR 0.34, 95% CI 0.21 to 0.55, eight studies, 1132 women). Both the 500 mg to 650 mg and 1000 mg doses were effective in providing more pain relief than placebo.Maternal and neonatal potential adverse drug effects were not assessed in any of the included studies. Indeed few secondary outcomes were assessed. AUTHORS' CONCLUSIONS: More women experienced pain relief, and fewer had additional pain relief, with paracetamol compared with placebo, although potential adverse effects were not assessed and generally the quality of studies was unclear.